Efeitos do treino funcional de alcance associado ao controle de tronco em lactentes pré-termo moderados a tardios: ensaio clínico randomizado e controlado - Zambello, Vanessa (Universidade Federal de São Carlos, 2023)
Introduction: Commonly, preterm infants have a delay in the acquisition of motor skills. Evidence has shown that reaching specific interventions and experiences in a variety of postures have improved reaching behavior, head control, and motor development in preterm infants. However, knowing that reaching and trunk control are interrelated skills, it is relevant to develop an intervention that emphasizes trunk control activities associated with reaching for the motor development of infants at biological risk. Objective: To investigate the effects of an early intervention protocols on gross motor performance, trunk control and reaching of moderate to late preterm infants at the emergence of reaching. Methods: Thirty-nine moderate- to late- preterm infants (34.82 ± 1.20 weeks of gestational age) (19 boys and 20 girls) at the onset of reaching (4.36 ± 0.54 months corrected age) were randomized into two groups: experimental - received training of functional reaching associated with trunk control and control– positioning training. Infants were assessed by the Segmental Assessment of Trunk Control (SATCo), Alberta Infant Motor Scale (AIMS) and reaching assessment in 4 assessments: 1) pre-training; 2) post-training 1; 3) post-training 2 and 4) retention. All assessments were performed by a blinded evaluator. The training of functional reaching associated with trunk control was performed by a physical therapist and parents at home for 12 consecutive days (6 sessions delivered by physical therapist and 6 sessions by parents) consisting of activities focused on trunk control and reaching activities in a variety of postures, for approximately 30-40 minutes a day. For the variables of gross motor performance, trunk control and reaching, the Mann-Whitney test was applied to compare the groups (experimental and control) in each assessment (pre-training, post-training 1 and 2 and retention). Results: Training functional reaching in association with trunk control was superior to positioning training, considering gross motor performance at post-training p= 0.023 and retention p= 0.005 and AIMS prone subscale at retention p= 0.002, a higher frequency of reaches with open hand at post-training 1 p <0.001 and with grasping at post-training 2, but not regarding trunk control, for the frequency of reaches, uni- and bimanual reaches, vertical, closed hand and contact surface (dorsal or ventral). Conclusion: Training functional reaching in association with trunk control was effective in favoring gross motor performance and increasing the frequency of more adaptive reaching, in other words, with an open hand and grasping, favoring the exploration of objects and which can be an efficient early intervention strategy for clinicians and parents.
Effects of training functional reaching in association with trunk control on moderate to late preterm infants: a randomized controlled clinical trial
Keywords: Prematuro; Desenvolvimento Motor; Intervenção precoce; Controle de tronco; Alcance manual; Premature; Motor development; Early intervention; Trunk control; Reaching; CIENCIAS DA SAUDE::MEDICINA::SAUDE MATERNO-INFANTIL